Design of macropore structure and micro-nano topography to promote the early neovascularization and osteoinductivity of biphasic calcium phosphate bioceramics. (April 2022) - Li, Xiangfeng; Wang, Yuyi; Chen, Fuying; Chen, Xuening; Xiao, Yumei; Zhang, Xingdong
Graphical abstract: BCP bioceramics with optimal design of macropore distribution and micro-nano topography to promote the early neovascularization and osteoinductivity. Highlights: BCP bioceramics with appropriately ordered macropores and nanocrystalline could well regulate angiogenic differentiation of HUVECs and osteogenic differentiation of BMSCs. The initial neovascularization followed by later osteogenesis are two main stages during bone regeneration, and the formation of mature vessels is a prominent feature prior to the occurrence of osteoinductivity of BCP bioceramics. The osteoinductivity of BCP bioceramics can be further enhanced by optimizing pore size distribution and micro-nano topography to meet the requirements of regenerative medicine. Abstract: Early neovascularization and osteoinductivity are two key factors to determine the regenerative abilities of biphasic calcium phosphate (BCP) bioceramics in bone repair. Due to the uncontrolled pore structure and large grain size, the biological performances of the conventional BCP bioceramics is restricted to a large extent. Herein, this study attempted to fabricate BCP bioceramics with appropriately uniform macropores and abundant micropores by combining the advantages of the H2 O2 foaming method with the microsphere-sintering method, and different sintering methods were adopted to adjust the micro-nano topography. Due to the optimal design of macropore distribution and nano topography, the obtained BCP bioceramics could well trigger and regulate in vitro biological responses, such as degradation, bone-like apatite formation, protein adsorption, cell spreading, angiogenic and osteogenic differentiation. In vivo canine intramuscular implantation further revealed that the nano topography and appropriately uniform macropores might be responsible for the early neovascularization and osteoinductivity of the prepared BCP bioceramics. Collectedly, the neovascularization and osteoinductivity of BCP bioceramics were further enhanced by optimally designing the pore structure and micro-nano topography, which hold huge potential to be an alternative to the gold standard of autogenous bone in bone repairing applications.